Perancangan Dan Pembuatan Sistem Peminjaman Dan Pengembalian Dokumen Rekam Medis Berbasis Website Di Rumah Sakit Gigi dan Mulut Universitas Jember - Wiranti Angelina Tabi; Bakhtiyar Hadi Prakoso; Rossalina Adi Wijayanti; Andri Permana Wicaksono (Indonesian Journal Publisher, 2024)
The process of borrowing and returning medical record documents at the Dental and Oral Hospital of the University of Jember is currently carried out manually using an expedition book. The absence of a tracer as a tool to track medical records makes it difficult for staff to locate borrowed documents, leading to misplaced documents in the filing racks. There are issues with late returns from clinics, which do not comply with the standard operating procedures for medical record document storage at the Dental and Oral Hospital of the University of Jember, and there is no record of these delays, resulting in a lack of problem documentation. The researcher aims to design and develop a web-based medical record borrowing and returning information system at the Dental and Oral Hospital of the University of Jember. The researcher used the waterfall development method, with data collection techniques including interviews, observations, documentation, and brainstorming. The results of the study show that the developed information system has several advantages, such as medical record barcode printing features, medical record tracers, and WhatsApp notifications as reminders for overdue medical record returns.